Métodos de conservación de la pasta de maní (Arachis hypogaea) - Ramos Mackliff, Lourdes Rocio (2011)
The present investigation has as aim evaluate the process of conservation of the pasta of peanut (Arachis hypogaea), whose factors of study are the time of storage, the temperature of storage and the method of conservation; the variables to be evaluating are the dampness, pH, aflatoxinas, aerobic total, coliformes total, fungi and yeasts. Taking as characteristics of the experiment 12 treatments, 3 repetitions, giving a total of 36 experimental units. For the statistical analysis (DCA) applied a Design to himself completely at random, with arrangement factorial AXBXC; whereas, to determine the difference between the levels of the factors in those who existed significancia Tukey's test was used to 5%. It was obtained as results, highly significant differences in the treatments the alternative hypothesis being accepted. With regard to the dampness, the treatments T5, T7, T11 and T8 are in an ideal level of acceptance, since they present percentages more down dampness (1,46 %, 1,48 %, 1,53 % respectively), the above mentioned information is not comes closer with exposed by Macintosh/Barry/Parr/Litster (1977), where they indicate that the percentage of dampness of the pasta of peanut is lower than 1 %. Opposite to the treatment T3, which has the highest percentage of dampness (2,29 %). For the pH, one determined that the treatments T5, T7, T3 and T1 (6,26 %, 6,27 % respectively) present a percentage of pH higher, which helps to disable the growth of microorganisms, unlike the treatments T10 and T4 (6,32 % and 6,33 % respectively) that the levels of pH are the lowest. In the levels of aflatoxinas, it was found that the treatments T7, T2, T1, T8, T9 and T5 are applicable in the method of conservation of the pasta of peanut for not presenting aflatoxinas, with regard to the treatment T10 that I present the highest level (1,17 ppb). Nevertheless they are inside the parameters indicated in the MERCOSUR/GMC/RES. N º 25/02, 2002, which indicates us that the maximum admissible limit of aflatoxinas in the pasta of peanut is of 20 ug/kg. For the Aerobic total bacteria, one determined that the treatments T2, T4 and T6 (2.43 x 102 UFC/gr ó cm3, 2.52 x 102 UFC/gr ó cm3, 2.60 x 102 UFC/gr ó cm3), considered acceptable for presenting the levels more down UFC/gr ó cm3, with reference to the treatment T11 that it is thought that he presents a pollution higher (6.53 x 102 UFC/gr ó cm3). Related to the indicated for the Colombian Norm INVIMA it expresses that the parameters of the aerobic mesófilos it is 10000 UFC/gr. ó cm3 Due to the fact that this norm is for the peanut. With regard to the total coliformes, the treatments did not present pollution of coliformes, whereas in the tratamiento T5 and T11 (2.35 x 102 UFC/gr ó cm3 and 2.50 x 102 UFC/gr ó cm3 respectively) pollution exists. On having related them to the indicated for the Colombian Norm INVIM, are they out of the límite of acceptance, since it expresses that the parameters for Coliformes it must be? 3 UFC/gr. ó cm3 Due to the fact that this norm is for the peanut. And for the Fungi and Yeasts, the treatments T7, T8, T6, T2, T1, T10, T4 and T2 are the ideal ones for the method of conservation of the pasta of peanut since they do not present pollution by these microorganisms, unlike the tratamiento T11 and T5 that are considered to be villains r the highest levels (2.10 x 102 UFC/gr ó cm3 and 2.50 x 102 UFC/gr ó cm3 respectively). The same ones, who on having related them to the indicated for the Colombian Norm INVIM, are inside the limit of acceptance, since it expresses that the parameters for fungi and yeasts must be 300 UFC/gr. ó cm3. This norm is for the peanut in strict sense